Soft tissue release - Johnson, Jane 1965- (Hands-on guides for therapists, 2009)
This book is a clear, concise, and practical book that guides you in understanding and applying the three types of soft tissue release (STR): passive (clients do not help), active assisted (clients and therapists work together), and active (clients do it on their own)